Establishment of an indirect ELISA method for antibody detection of porcine pseudorabies by recombinant gB, gC, and gD proteins. Issue 1 (10th November 2022) - Wu, Xuemin; Chen, Rujing; Chen, Qiuyong; Che, Yongliang; Yan, Shan; Zhou, Lunjiang; Wang, Longbai
Abstract: Pseudorabies virus (PRV), as a neuroherpes virus, leads to heavy economic losses in the pig industry worldwide. This study was designed to establish recombinant PRV glycoprotein B (gB), C, and D proteins as PRV diagnostic antigens. The gB/C, gC/D, and gB/C/D fusion sequences were synthesized and inserted into pET‐28a + vector to generate the recombinant plasmids. The identified positive recombinant plasmids were transformed into BL21 Escherichia coli . The results of the polymerase chain reaction and enzyme digestion showed that the gB/C, gC/D, and gB/C/D fusion proteins were successfully expressed. An indirect sandwich ELISA was developed with the gB/C, gC/D, and gB/C/D as coating antigens. The results of indirect enzyme‐linked immunosorbent assay (ELISA) analysis of 184 PRV‐positive porcine sera showed that the positive coincidence rates of three recombinant proteins ELISAs relative to IDEXX kit were 98.25%, 95.32%, and 98.83%, and the negative coincidence rates were 85.71%, 75% and 100%, respectively. The inter and intra batch repeatability tests showed that the coefficient of variations of our kits were all less than 5%. Especially, the gB/C/D‐ELISA has the highest specificity and sensitivity among the ELISA methods developed in this study. We established a series expression system of gB/C, gC/D, and gB/C/D antigen epitope genes and Recombinant protein‐based indirect ELISA, providing new ideas for PV diagnosis and vaccine development.